A kind of ultra-high pore density alumina honeycomb ceramic carrier and preparation method thereof
By using narrow particle size distribution sheet talc, low-grain flake kaolin and spherical alumina powder, combined with specific binders and reagents, the problems of pore defects and low mechanical strength of alumina honeycomb ceramic carriers are solved, achieving high Preparation of ceramic carriers with pore density and high mechanical properties, suitable for high-efficiency filtering materials.
Patent Information
- Application Number
- CN202411488019.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing alumina honeycomb ceramic carriers have problems such as large pore defects and low mechanical strength of the blank, which leads to prone to cracking and increased costs during the firing process.
Use flake talc with narrow particle size distribution, low-grain flake water-washed kaolin and narrow particle size distribution spherical alumina powder as inorganic solid raw materials, combined with carboxymethylcellulose as binder, and use polyethyleneimine and fatty acids. As an organic reagent, sodium is formed by uniform mixing and wet kneading, extruded into a honeycomb structure, and the firing temperature is controlled at 1540~1600℃ to reduce pore defects and improve mechanical properties.
The preparation of ultra-high pore density alumina honeycomb ceramic carrier is realized, reducing pore defects, improving mechanical properties and thermal stability, enhancing flexural strength and compressive strength, and is suitable for high-performance filter materials.
Smart Images

Figure CN118993759B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of honeycomb ceramic materials, and in particular relates to an ultra-high pore density alumina honeycomb ceramic carrier and a preparation method thereof. Background Art
[0002] In recent years, my country has attached increasing importance to environmental quality, clean production, energy conservation and emission reduction. Environmental protection standards have been continuously improved, environmental supervision and law enforcement have been strengthened, special emissions and ultra-low emissions have become normalized, and downstream customers have a broad demand for high-performance filter materials. On the other hand, the country has issued a series of laws and industrial policy documents to provide a good policy environment for the development of the environmental protection industry. Under the guidance of national policies such as "carbon peak" and "carbon neutrality", the downstream market's demand for high-efficiency filter materials with excellent performance and adaptability to harsh environments will continue to grow. At the same time, industrial waste gas treatment, biomass combustion, petroleum catalytic cracking and other fields have also put forward higher requirements for high-performance catalytic carriers. As a porous material, the ultra-high pore density alumina honeycomb ceramic carrier has the properties of high temperature resistance, corrosion resistance, high strength and good thermal stability. At the same time, it has an ultra-high specific surface area and a special pore structure, which can better improve its catalytic efficiency and purification capacity, and conform to the future market trend of high demand for gas-gas exchange, gas-liquid exchange, and liquid-liquid exchange material carriers.
[0003] The current traditional alumina honeycomb ceramic carriers are made of flaky talc, flaky kaolin, and flaky alumina raw materials. The flaky raw materials are arranged in a directional manner during extrusion, and the morphology, particle size, diameter-to-thickness ratio, and purity of the raw materials are strictly required. This not only greatly limits the selection of raw materials, but also, due to the coarse particle size in the molding process, mold clogging, high pressure, and molding difficulties will occur when the mud section passes through a high-pore density mold. The existing solution is generally to increase the amount of lubricants such as alkanes, fatty acids, and other organic solvents to improve dispersibility and lubricity. However, with the increase in the amount of binders and lubricants, the cost rises sharply, and it also brings difficulties in firing. When a large amount of organic additives are thermally decomposed at low temperature, a large amount of heat is generated. Due to the thinning of the wall thickness of the alumina honeycomb ceramic carrier, the porosity increases, and the mechanical strength of the green body decreases, which easily causes the green body to crack during the firing process. Summary of the invention
[0004] The invention relates to a method for preparing an ultra-high pore density alumina honeycomb ceramic carrier, so as to solve the problems of large pore defects and low mechanical strength of green bodies in the prior art.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] The present invention provides a method for preparing an ultra-high pore density alumina honeycomb ceramic carrier, wherein the honeycomb ceramic carrier is prepared by using mud material, and the mud material comprises an inorganic solid raw material, an organic binder, an organic reagent and water;
[0007] The inorganic solid raw materials include flaky talc with narrow particle size distribution, low particle size flaky washed raw kaolin, and spherical alumina powder with narrow particle size distribution;
[0008] The diameter-to-thickness ratio of the narrow particle size distribution flaky talc is 5-20:1, and the particle size D 50 1.5~2.5μm, particle size D 97 Less than or equal to 10μm;
[0009] The low-particle-size flaky washed raw kaolin has a diameter-to-thickness ratio of 10 to 30:1 and a particle size of D 50 1~3μm, particle size D 97 Less than or equal to 15μm;
[0010] The particle size D of the narrow particle size distribution spherical alumina powder 50 2~4μm, particle size D 97 Less than or equal to 10 μm, in the spherical alumina powder, Al 2 O 3 The mass percentage is greater than or equal to 99.5%.
[0011] Based on the above technical solution, the present invention can also be improved as follows.
[0012] Furthermore, the mass percentages of the components in the inorganic solid raw material are: 41.68% to 44.25% of the narrow particle size distribution flaky talc, 16.54% to 30.17% of the low particle size flaky washed raw kaolin, and 17.58% to 24.39% of the narrow particle size distribution spherical alumina powder.
[0013] Furthermore, the organic reagent includes polyethyleneimine, a molding release agent, and sodium fatty acid.
[0014] Furthermore, the organic binder is carboxymethyl cellulose.
[0015] Furthermore, taking the mass of the inorganic solid raw material as 100%, the mass percentage of carboxymethyl cellulose is 4-8%, the mass percentage of water is 12-18%, the mass percentage of polyethyleneimine is 0.25-0.75%, the mass percentage of the molding release agent is 1-3%, and the mass percentage of sodium fatty acid is 1-3%.
[0016] Furthermore, the preparation method of the narrow particle size distribution spherical alumina powder is to melt any one or more of the classified ordinary flaky alumina powder, angular α alumina powder, and aluminum hydroxide powder at a temperature greater than 2000°C, and obtain the spherical alumina powder after cooling.
[0017] Furthermore, the method comprises the following steps: firstly, uniformly mixing the inorganic solid raw material and the binder, then adding water and the organic reagent for wet mixing and kneading to obtain the mud material; kneading the mud material into mud segments with plasticity, then extruding the mud segments into a honeycomb structure, and then sequentially drying, cutting, sintering and cooling to obtain the honeycomb ceramic carrier.
[0018] Furthermore, the sintering temperature is 1540-1600° C., and the sintering holding time is 8-15 hours.
[0019] The present invention also provides an ultra-high pore density alumina honeycomb ceramic carrier, which is prepared by the above-mentioned preparation method.
[0020] Furthermore, the pore density of the ultra-high pore density alumina honeycomb ceramic carrier is 10000-30000 meshes.
[0021] The beneficial effects of the present invention are:
[0022] (1) The method for preparing the ultra-high pore density alumina honeycomb ceramic carrier of the present invention uses inorganic solid raw materials, and the spherical alumina with narrow particle size distribution has more uniform sintering shrinkage due to similar particle sizes, thereby reducing pore defects caused by uneven shrinkage, such as excessively large pores or uneven pore distribution;
[0023] (2) The method for preparing the ultra-high pore density alumina honeycomb ceramic carrier of the present invention uses spherical alumina with narrow particle size distribution, flaky talc with narrow particle size distribution, and low-particle size flaky washed raw kaolin to make the particles more densely packed, which helps to form a uniform pore size distribution, improves the thermal conductivity of the ceramic carrier, and is conducive to the rapid transfer of heat;
[0024] (3) The ultra-high pore density alumina honeycomb ceramic carrier of the present invention has a uniform pore structure and a high porosity, so that the honeycomb ceramic carrier has better mechanical properties, such as higher bending strength and compressive strength, thereby effectively increasing the service life and stability of the ceramic carrier.
[0025] (4) The ultra-high pore density alumina honeycomb ceramic carrier of the present invention has a pore density of 10,000-30,000 meshes. As a high-performance filter material carrier, it has high filtration accuracy and efficiency, thermal stability and adaptability to harsh environments. It is applicable to a wide range of fields, especially in the direction of medium exchange, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of flaky talc with a narrow particle size distribution in the method for preparing an ultra-high pore density alumina honeycomb ceramic carrier of the present invention;
[0027] Figure 2This is a SEM image of low-particle-size flaky washed raw kaolin in the method for preparing the ultra-high pore density alumina honeycomb ceramic carrier of the present invention;
[0028] Figure 3 This is a SEM image of spherical alumina with narrow particle size distribution in the method for preparing the ultra-high pore density alumina honeycomb ceramic carrier of the present invention. DETAILED DESCRIPTION
[0029] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0030] The invention discloses a method for preparing an ultra-high pore density alumina honeycomb ceramic carrier. The honeycomb ceramic carrier is prepared by using a mud material. The mud material comprises an inorganic solid raw material, an organic binder, an organic reagent and water. The inorganic solid raw material comprises a narrow particle size distribution flaky talc, a low particle size flaky washed raw kaolin and a narrow particle size distribution spherical alumina powder. The diameter-to-thickness ratio of the narrow particle size distribution flaky talc is 5-20:1, and the particle size D 50 1.5~2.5μm, particle size D 97 Less than or equal to 10μm; low-particle flaky washed raw kaolin diameter-to-thickness ratio is 10~30:1, particle size D 50 The particle size D97 is less than or equal to 15 μm; the particle size D of the spherical alumina powder with narrow particle size distribution is 50 2~4μm, particle size D 97 Less than or equal to 10μm, in spherical alumina powder, Al 2 O 3 The mass percentage is greater than or equal to 99.5%.
[0031] The method for preparing the ultra-high pore density alumina honeycomb ceramic carrier of the present invention utilizes spherical alumina powder with a narrow particle size distribution to synthesize the ultra-high pore density honeycomb ceramic carrier. Since the particle sizes of the spherical alumina are similar, the sintering shrinkage is more uniform, which reduces the pore defects caused by uneven shrinkage of the particles, such as excessive pores or uneven pore distribution. The use of spherical alumina with a narrow particle size distribution, flaky talc with a narrow particle size distribution, and low-particle-size flaky washed raw kaolin can make the particles stack more tightly, help to form a uniform pore size distribution, improve the thermal conductivity of the ceramic carrier, and facilitate the rapid transfer of heat. The uniform pore structure and higher porosity often mean better mechanical properties, such as higher flexural strength and compressive strength, which significantly improves the service life and stability of the ceramic carrier.
[0032] In one embodiment of the present invention, the SEM image of the narrow particle size distribution flaky talc is as follows: Figure 1 As shown, the SEM image of low-particle-size flaky washed raw kaolin is as follows Figure 2As shown, the SEM image of spherical alumina powder is as follows Figure 3 shown.
[0033] Preferably, the organic binder is carboxymethyl cellulose (MC), and the organic reagent includes purified water, polyethyleneimine, a molding release agent, and sodium fatty acid.
[0034] Preferably, the low-particle-size flaky washed raw kaolin is processed by crushing and grinding the kaolin ore particles, classifying and removing impurities, ultra-fine processing, and flaking to maintain its flaky structure.
[0035] Preferably, the method for preparing spherical alumina powder with narrow particle size distribution is as follows: the classified common flake α alumina powder, angular α alumina powder and aluminum hydroxide powder are conveyed into a high temperature flame furnace above 2000°C, the alumina powder is instantly melted in the flame, the melted alumina powder is spherical due to surface tension, and then quickly transferred to a freezing casting device, usually cooled and collected at a liquid nitrogen temperature below -196°C, so that spherical alumina powder with smaller grains can be obtained, and the particle size D 50 2~4μm, particle size D 97 Less than or equal to 10μm, containing Al 2 O 3 The content is greater than or equal to 99.5%.
[0036] Preferably, in the inorganic solid raw material, the mass percentage of each component is 41.68% to 44.25% of flaky talc with narrow particle size distribution, 16.54% to 30.17% of low particle size flaky washed raw kaolin, and 17.58% to 24.39% of spherical alumina powder with narrow particle size distribution.
[0037] Preferably, the organic binder is carboxymethyl cellulose (MC).
[0038] Preferably, the organic agent includes polyethyleneimine, a molding release agent, and sodium fatty acid.
[0039] Polyethylenimine is used as a dispersant. Polyethylenimine is a cationic water-soluble macromolecular organic substance that can adjust the interfacial charge, enhance the repulsive force between particles, prevent agglomeration and sedimentation between particles, and form a protective film on the surface of the particles through electrostatic stabilization and steric hindrance, which hinders direct contact between particles, thereby maintaining the dispersed state of the particles, which is beneficial to the subsequent molding process.
[0040] Using molding release agent as lubricant can improve the plasticity and lubricity of extruded products, reduce molding pressure, improve the appearance of high-pore density and thin-walled products, effectively reduce the wear of molding equipment and molds, reduce water demand, shorten microwave drying time, reduce energy consumption, reduce drying shrinkage, and reduce microwave cracking.
[0041] Preferably, the mass percentage of the inorganic solid raw material is 100%, the mass percentage of carboxymethyl cellulose is 4-8%, the mass percentage of water is 12-18%, the mass percentage of polyethyleneimine is 0.25-0.75%, the mass percentage of the molding release agent is 1-3%, and the mass percentage of sodium fatty acid is 1-3%.
[0042] Preferably, the water is purified water.
[0043] The preparation method of the present invention comprises the following steps:
[0044] First, the inorganic solid raw materials and the binder are dry-mixed for 17-30 minutes using an inclined weightless mixing device to fully mix them, and water and organic reagents are added and wet-mixed for 30 minutes to form a clay material with appropriate plasticity and viscosity. The double-shaft speed of the kneading machine is set to 20 r / min; the clay material is further kneaded, stretched, and sheared by a clay training machine to form a clay segment with appropriate hardness, and the clay segment is extruded into a honeycomb structure. The product is extruded using a crawler microwave device and microwave-dried to obtain a green body; the green body is then end-face cut and polished, and then placed in a shuttle automatic kiln for firing at a firing temperature of 1540~1600℃ and a firing insulation time of 8~15 hours to obtain an ultra-high pore density alumina honeycomb ceramic carrier.
[0045] Preferably, the sintering temperature is 1600° C. and the sintering holding time is 12 hours.
[0046] The high-strength and high-porosity honeycomb ceramic carrier of the present invention has a pore density of 10,000-30,000 meshes and has high filtering accuracy and efficiency, thermal stability and adaptability to harsh environments.
[0047] The present invention is illustrated below by means of specific examples.
[0048] Examples 1 to 9 are honeycomb ceramic carriers with ultra-high pore density of the present invention. Table 1 shows the particle size, aspect ratio, morphology, and specific chemical composition parameters of the inorganic solid raw materials used in each example. The narrow particle size distribution flaky talc is specifically talc A1, talc A2, and talc A3, the low particle size flaky washed raw kaolin is kaolin B1, kaolin B2, and kaolin B3, and the narrow particle size distribution spherical alumina powder is alumina powder C1, alumina powder C2, and alumina powder C3.
[0049] Table 2 shows the mass percentage of each specific component in the inorganic solid raw material used in each embodiment, as well as the mass fractions of organic reagents and water.
[0050] The honeycomb ceramic carrier of the comparative example has the following mud components: 3.55% talc, 1.72% hydrated clay, 94.73% white corundum, 7% polymethyl methacrylate, 5.5% polyvinyl alcohol, 1.2% emulsified oil, and 25% water.
[0051] Table 1 Parameters of particle size, aspect ratio, morphology, and specific chemical composition of the inorganic solid raw materials used in Examples 1 to 9
[0052]
[0053] Table 2 Mass percentage of each specific component of Examples 1 to 9 and mass fractions of organic reagents and water
[0054]
[0055] Table 3 Comparison of performance of alumina honeycomb ceramic substrate
[0056]
[0057] Note: For product appearance, “+” indicates good, and the more “+”s, the better. “-” indicates poor, and the more “-”s, the worse.
[0058] Table 3 is a performance comparison of the alumina honeycomb ceramic carriers prepared in various embodiments and comparative examples, mainly involving the firing qualification rate, firing shrinkage rate, and extrusion mesh range.
[0059] It can be seen from Table 3 that, compared with Examples 1 to 3, with the increase of molding release agent and sodium stearate, the plasticity, lubricity and fluidity of the mud material are getting better and better, the molding extrusion pressure is reduced, the extrusion speed is accelerated, and the carrier appearance is better.
[0060] By comparing Examples 4 to 9, it can be seen that with the increase of organic additives, a large amount of heat is released during the low-temperature sintering process, thereby reducing the qualified rate of the product. With the increase of the number of pores in the extruded product, the weight increases, the extrusion pressure increases, the extrusion speed slows down, and the internal defects increase, resulting in a deterioration in the appearance of the product. By fine-tuning the addition ratio of spherical alumina, the sintering qualified rate of Examples 1 to 9 reaches 97.1% to 100%, and has a higher porosity. The high pore density carrier has a huge specific surface area, which meets the requirements of high specific surface area, high pore size and high porosity of the high-efficiency filtration material, and the product performance is much higher than that of the comparative example.
[0061] In the description of the present invention, it should be noted that the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an ultra-high pore density alumina honeycomb ceramic carrier, characterized in that: The honeycomb ceramic carrier is prepared by using mud material, and the mud material includes inorganic solid raw materials, organic binder, organic reagent and pure water; First, the inorganic solid raw material and the organic binder are uniformly mixed, and then purified water and the organic reagent are added for wet mixing and kneading to obtain the mud material; the mud material is kneaded into a plastic mud segment, and then the mud segment is extruded into a honeycomb structure, and then dried, cut, sintered and cooled in sequence to obtain the honeycomb ceramic carrier; The sintering temperature is 1540-1600°C and the holding time is 8-15 hours; The inorganic solid raw materials include flaky talc with narrow particle size distribution, low particle size flaky washed raw kaolin, and spherical alumina powder with narrow particle size distribution; the organic reagents include polyethyleneimine, a molding release agent, and sodium stearate; the organic binder is carboxymethyl cellulose, and the mass percentage of the carboxymethyl cellulose is 4-8% based on the mass of the inorganic solid raw materials being 100%; The components of the mud are: The diameter-to-thickness ratio of the narrow particle size distribution flaky talc is 30:1, and the particle size D 10 0.86μm, particle size D 50 2.12 μm, particle size D 97 The low-particle-size flaky washed raw kaolin has a diameter-to-thickness ratio of 4:1 and a particle size D 10 0.25 μm, particle size D 50 1.78 μm, particle size D 97 The narrow particle size distribution spherical alumina powder has a particle size D 10 0.52μm, particle size D 50 2.13 μm, particle size D 97 The particle size of the inorganic solid raw material is 6.53 μm, and the mass percentage of Al2O3 is 99.7%; the mass percentage of each component in the inorganic solid raw material is 2.26% of the narrow particle size distribution flaky talc, 5.86% of the low particle size flaky washed raw kaolin, and 91.88% of the narrow particle size distribution spherical alumina powder; the mass percentage of the inorganic solid raw material is 100%, the mass percentage of polyethyleneimine is 0.25%, the mass percentage of the molding release agent is 1%, the mass percentage of sodium stearate is 1%, and the mass percentage of pure water is 13%; the pore density of the ultra-high pore density alumina honeycomb ceramic carrier is 10064 mesh; Or, the diameter-to-thickness ratio of the narrow particle size distribution flaky talc is 30:1, and the particle size D 10 0.86μm, particle size D 50 2.12 μm, particle size D 97 The low-particle-size flaky washed raw kaolin has a diameter-to-thickness ratio of 16:1 and a particle size D 10 0.41 μm, particle size D 50 2.26 μm, particle size D 97 8.24 μm; the narrow particle size distribution spherical alumina powder, particle size D 10 0.84 μm, particle size D 50 2.85 μm, particle size D 97 The particle size of the inorganic solid raw material is 7.22 μm, and the mass percentage of Al2O3 is 99.6%; the mass percentage of each component in the inorganic solid raw material is 1.4% of the narrow particle size distribution flaky talc, 5.75% of the low particle size flaky washed raw kaolin, and 92.85% of the narrow particle size distribution spherical alumina powder; the mass percentage of the inorganic solid raw material is 100%, the mass percentage of polyethyleneimine is 0.25%, the mass percentage of the molding release agent is 1.2%, the mass percentage of sodium stearate is 1.2%, and the mass percentage of pure water is 13%; the pore density of the ultra-high pore density alumina honeycomb ceramic carrier is 10028 mesh; Or, the diameter-to-thickness ratio of the narrow particle size distribution flaky talc is 30:1, and the particle size D 10 0.86μm, particle size D 50 2.12 μm, particle size D 97 The low-particle-size flaky washed raw kaolin has a diameter-to-thickness ratio of 30:1 and a particle size D 10 0.68 μm, particle size D 50 2.69 μm, particle size D 97 10.31 μm; the narrow particle size distribution spherical alumina powder, particle size D 10 1.03 μm, particle size D 50 3.41 μm, particle size D 97 The particle size of the inorganic solid raw material is 8.64 μm, and the mass percentage of Al2O3 is 99.8%; the mass percentage of each component in the inorganic solid raw material is 0.73% of the narrow particle size distribution flaky talc, 5.58% of the low particle size flaky washed raw kaolin, and 93.69% of the narrow particle size distribution spherical alumina powder; the mass percentage of the inorganic solid raw material is 100%, the mass percentage of polyethyleneimine is 0.25%, the mass percentage of the molding release agent is 1.5%, the mass percentage of sodium stearate is 1.5%, and the mass percentage of pure water is 14%; the pore density of the ultra-high pore density alumina honeycomb ceramic carrier is 10151 mesh; Or, the diameter-to-thickness ratio of the narrow particle size distribution flaky talc is 50:1, and the particle size D 10 1.03 μm, particle size D 50 2.28 μm, particle size D 97 The low-particle-size flaky washed raw kaolin has a diameter-to-thickness ratio of 30:1 and a particle size D 10 0.68 μm, particle size D 50 2.69 μm, particle size D 97 10.31 μm; the narrow particle size distribution spherical alumina powder, particle size D 10 0.52μm, particle size D 50 2.13 μm, particle size D 97 The particle size of the inorganic solid raw material is 6.53 μm, and the mass percentage of Al2O3 is 99.7%; the mass percentage of each component in the inorganic solid raw material is 3.75% of the narrow particle size distribution flaky talc, 5.34% of the low particle size flaky washed raw kaolin, and 90.91% of the narrow particle size distribution spherical alumina powder; the mass percentage of the inorganic solid raw material is 100%, the mass percentage of polyethyleneimine is 0.25%, the mass percentage of the molding release agent is 1.8%, the mass percentage of sodium stearate is 1.8%, and the mass percentage of pure water is 14%; the pore density of the ultra-high pore density alumina honeycomb ceramic carrier is 20164 mesh; Or, the diameter-to-thickness ratio of the narrow particle size distribution flaky talc is 50:1, and the particle size D 10 1.03 μm, particle size D 50 2.28 μm, particle size D 97 The low-particle-size flaky washed raw kaolin has a diameter-to-thickness ratio of 16:1 and a particle size D 10 0.41 μm, particle size D 50 2.26 μm, particle size D 97 8.24 μm; the narrow particle size distribution spherical alumina powder, particle size D 10 0.84 μm, particle size D 50 2.85 μm, particle size D 97 The particle size of the inorganic solid raw material is 7.22 μm, and the mass percentage of Al2O3 is 99.6%; the mass percentage of each component in the inorganic solid raw material is 3.95% of the narrow particle size distribution flaky talc, 3.67% of the low particle size flaky washed raw kaolin, and 92.38% of the narrow particle size distribution spherical alumina powder; the mass percentage of the inorganic solid raw material is 100%, the mass percentage of polyethyleneimine is 0.25%, the mass percentage of the molding release agent is 2%, the mass percentage of sodium stearate is 2%, and the mass percentage of pure water is 13%; the pore density of the ultra-high pore density alumina honeycomb ceramic carrier is 20189 mesh; Or, the diameter-to-thickness ratio of the narrow particle size distribution flaky talc is 50:1, and the particle size D 10 1.03 μm, particle size D 50 2.28 μm, particle size D 97 The low-particle-size flaky washed raw kaolin has a diameter-to-thickness ratio of 4:1 and a particle size D 10 0.25 μm, particle size D 50 1.78 μm, particle size D 97 The narrow particle size distribution spherical alumina powder has a particle size D 10 1.03 μm, particle size D 50 3.41 μm, particle size D 97 The particle size of the nanostructured carbon foam is 8.64 μm, and the mass percentage of Al2O3 is 99.8%; in the inorganic solid raw material, the mass percentage of each component is 3.82% of the narrow particle size distribution flaky talc, 2.42% of the low particle size flaky washed raw kaolin, and 93.76% of the narrow particle size distribution spherical alumina powder; taking the mass of the inorganic solid raw material as 100%, the mass percentage of polyethyleneimine is 0.35%, the mass percentage of the molding release agent is 2%, the mass percentage of sodium stearate is 2%, and the mass percentage of pure water is 14%; the pore density of the ultra-high pore density alumina honeycomb ceramic carrier is 20215 mesh.
2. The method for preparing an ultra-high pore density alumina honeycomb ceramic substrate according to claim 1, characterized in that: The method for preparing the narrow particle size distribution spherical alumina powder is to melt any one or more of the classified ordinary flaky alumina powder, angular α alumina powder, and aluminum hydroxide powder at a temperature greater than 2000° C. and obtain the spherical alumina powder after cooling.
3. An ultra-high pore density alumina honeycomb ceramic carrier, characterized in that: The preparation method according to claim 1 or 2 is used for preparation.